Residual feed intake in late-laying hens: immune function, metabolic efficiency, and feed utilization dynamics - Gao, Zhouyang; Mao, Zhiqiong; Xuan, Lin; Ma, Guoming; Wu, Yan; Xu, Guiyun (Frontiers in Veterinary Science, 2025)
The selection of high feed-efficiency animals is essential to address the increasing global demand for animal-derived products while ensuring sustainability. Residual Feed Intake (RFI), a crucial metric in poultry production, enhances feed utilization, optimizes management strategies, and promotes economic viability and environmental stewardship. However, the mechanisms underlying RFI variation remain inadequately understood. This study examined the regulatory pathways of RFI in 70-week-old Rhode Island Red laying hens through comparative analysis of phenotypic parameters, organ characteristics, and serum biochemical profiles between low-RFI (LRFI) and high-RFI (HRFI) groups. The findings demonstrate that RFI functions as a reliable indicator for feed efficiency selection, with LRFI hens demonstrating enhanced immune modulation and metabolic homeostasis while maintaining equivalent egg production performance. These results establish fundamental insights for understanding RFI regulatory mechanisms and developing precision breeding strategies for feed-efficient laying hens.